Mémoires d’origine et gestion communautaire de l’intégration en Tunisie (XVIIe-XIXe siècles) - Abdelhamid Hénia (EtnoAntropologia)
This contribution is focused on the two different models of communal management of integration existing in Tunisia respectively in the North and in the South of the Country. It is firstly ascertained the existence of models of integration based on the idea of the pre-eminence of the “extraneousness” in the South and on the antiquity of the autochthony in the North. It is after given some answers to questions concerning the exactness of the geographical division itself, the margins of negotiation differently emerging in the two models, the social implications of these forms of communal management of integration and the meaning to give to the change in status of the “extraneousness”.